Civic Education Teacher’s Attitudes Toward the Inclusion of Students with Specific Learning Disorders: A Field Study in Inclusive Public Schools in North Lebanon - Youssef , Dr. Wafaa Youssef (مجلة الشرق الأوسط للعلوم التربوية والنفسية, 2025)
This study investigates the attitudes of civic education teachers in elementary schools toward the inclusion of students with Specific Learning Disorders (SLDs) within inclusive educational settings, focusing on civic education classes. The research adopts a descriptive survey methodology and involves a sample of 112 teachers, randomly selected from inclusive public schools. A multidimensional psychometric tool was developed to assess cognitive-academic, social-interactive, psychological-emotional, and practical skills dimensions of teachers’ attitudes. The findings reveal generally positive attitudes toward inclusion, with slight differences favoring female teachers, younger teachers, and those holding a master’s degree. No statistically significant differences were found regarding teaching experience. Specialized training was found to have a significant positive effect on teachers’ attitudes toward effective inclusion practices